Range and niche shifts in response to past climate change in the desert horned lizard Phrynosoma platyrhinos. Issue 5 (2nd June 2015) - Jezkova, Tereza; Jaeger, Jef R.; Oláh‐Hemmings, Viktória; Jones, K. Bruce; Lara‐Resendiz, Rafael A.; Mulcahy, Daniel G.; Riddle, Brett R.
Abstract : During climate change, species are often assumed to shift their geographic distributions (geographic ranges) in order to track environmental conditions – niches – to which they are adapted. Recent work, however, suggests that the niches do not always remain conserved during climate change but shift instead, allowing populations to persist in place or expand into new areas. We assessed the extent of range and niche shifts in response to the warming climate after the Last Glacial Maximum (LGM) in the desert horned lizard Phrynosoma platyrhinos, a species occupying the western deserts of North America. We used a phylogeographic approach with mitochondrial DNA sequences to approximate the species range during the LGM by identifying populations that exhibit a genetic signal of population stability versus those that exhibit a signal of a recent (likely post‐LGM) geographic expansion. We then compared the climatic niche that the species occupies today with the niche it occupied during the LGM using two models of simulated LGM climate. The genetic analyses indicated that P. platyrhinos persisted within the southern Mojave and Sonoran deserts throughout the latest glacial period and expanded from these deserts northwards, into the western and eastern Great Basin, after the LGM. The climatic niche comparisons revealed that P. platyrhinos expanded its climatic niche after the LGM towards novel, warmer and drier climates that allowed it to persist within the southern deserts. Simultaneously, the species shifted its climatic niche towards greater temperature and precipitation fluctuations after the LGM. We concluded that climatic changes at the end of the LGM promoted both range and niche shifts in this lizard. The mechanism that allowed the species to shift its niche remains unknown, but phenotypic plasticity likely contributes to the species ability to adjust to climate change.